Needful things [compact disc, unabridged] - King, Stephen, 1947- (HighBridge Audio, 2008)
Seemingly harmless Leland Gaunt has just opened a store in Castle Rock, Maine, called 'Needful Things.' Curiously, he doesn't accept cash for purchases, but instead allows his customers to pay by playing small pranks on fellow townspeople. While the pranks start out as innocuous jokes, they soon build into harmful occurrences. Leland's influence soon has this once peaceful town in the midst of murderous turmoil.